The solution of Riccati type differential equation by means of variable step size backward difference methods - Rasedee, Ahmad Fadly Nurullah; Suleiman, Mohamed; Ahmadian, Ali; Ibrahim, Zarina Bibi; Othman, Khairil Iskandar; Rakhimov, Abdumalik (ISPACS, 2016)
In this article a variable order variable step size technique in backward difference form is used to solve non linear Riccati differential equation directly.